PRR-Mediated Immune Response and Intestinal Flora Profile in Soybean Meal-Induced Enteritis of Pearl Gentian Groupers, Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂ - Zhang, Wei; Tan, Beiping; Deng, Junming; Yang, Qihui; Chi, Shuyan; Pang, Aobo; Xin, Yu; Liu, Yu; Zhang, Haitao (Frontiers in Immunology, 2022)
Pattern recognition receptors (PRRs) can recognize microbial-specific pathogen-associated molecular patterns, initiate signal cascade transduction, activate the expressions of host immunity and pro-inflammatory genes and, ultimately, trigger an immune response against identified pathogens. The present study focused on two outcomes of feeding pearl gentian groupers with high levels of soybean meal (SBM): 1) growth performance and 2) the intestinal environment, including tissue structure, flora profile, and immune responses. Some 720 groupers were randomly divided into three groups (n = 4): 1) FM (controls, fed a 50% fishmeal feed), 2) SBM20 (with 20% of the FM substituted with SBM), and 3) SBM40 (40% of the FM substituted with SBM). The fish were fed these iso-nitrogenous and iso-lipidic diets for ten weeks. They were kept in containers with 1 m3 of water under natural light and temperature levels. The experimental results demonstrate that the SBM diets significantly degraded growth performance and intestinal physiology. Typical enteritis characteristics and immune fluctuations appeared, as reflected by the enzyme activities of total superoxide dismutase and lysozyme, and the contents of immunoglobulin M, complement 3, and complement 4. 16SrDNA high-throughput sequencing showed that the intestinal flora was significantly affected, with the abundance of harmful bacteria, such as Vibrio and Streptococcus, increasing with dietary SBM level. Based on “3+2” full-length transcriptome sequencing, three triggered PRRs were found in the intestine: the RIG-like receptor, NOD-like receptor, and Toll-like receptor signaling pathways. The intestinal flora variations were significantly correlated with the activation of the three PRRs signaling pathways by canonical correlation analysis. These culminated in the transcriptome activation of NF-κB, IRFs, and costimulatory molecules, ultimately promoting the expressions of pro-inflammatory cytokines, interferons (IFNs), chemokines, and other molecules vital to the innate and/or adaptive immune responses. This study provides new information for diagnosing and preventing SBMIE in aquaculture fish.